Կալիֆոռնիայի թեմի հիմնադրման եւ գործունէութեան հարցի շուրջ (1920—1930-ական թթ.) - Եսայեան, Յասմիկ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Основание епархий Армянской Апостольской Церкви в странах, где проживала армянская диаспора, происходило по-разному. Большое влияние на это оказывало характерное для армянской действительности жесткое противостояние политических организаций, которое еще более усилилось с установлением в Армении советской власти. В статье на основе неиспользованных ранее источников рассматривается начальный период истории епархии в Калифорнии, в контексте стремления партий «Дашнакцутюн» и «Рамкавар Азатакан» к контролю над церковью – важнейшему институту армянских общин. In the Armenian Diaspora, the establishment of dioceses of the Armenian Apostolic Church in different countries occurred in different ways. This was greatly influenced by the harsh opposition of political organizations, typical of the Armenian reality, which intensified with the establishment of the Soviet rule in Armenia. The article examines the early history of the diocese in California, based on previously unused sources, in the context of the aspiration of the Armenian political organizations — Armenian Revolutionary Federation and Democratic Liberal Party — to control the church, the most important institute in the Armenian Communities.
Keywords: Կրօնագիտութիւն